Antibiotic use in a co-infection of respiratory syncytial virus and pathogenic bacteria in children in a resource-limited setting in northeast Peninsular Malaysia - Liew, Constance Sat Lin; Rhanye Mac Guad; Taylor-Robinson, A.W; Kew, Seih Teck; Mandrinos, S; Elsonmond Vick Duin; Mexmollen Marcus; Chua, Shee Wen; Ho, Hui Lian; Lo, Zhen Zhen; Gan, S.H.; Wu, Y.S.; et al. (Malaysian Society of Parasitology and Tropical Medicine, 2024)
To investigate co-infection of bacterial isolates associated with respiratory syncytial virus (RSV) in children aged less than two years who were admitted to hospital with confirmed lower respiratory tract infection (LRTI) in Kelantan, Malaysia. The demographic data, clinical history, case management, haematological as well as infectious parameters (white blood cell differential and count, plus C-reactive protein, CRP) of the patients were systematically recorded. Less than one-third of cases were RSV-positive (21.03% and 26.23% were diagnosed as acute bronchiolitis or pneumonia, respectively). Blood cultures from approximately 10% of patients demonstrated growth of Haemophilus influenzae, Staphylococcus aureus, coagulase-negative Staphylococcus, Pseudomonas stutzeri, haemolytic Streptococcus group A, and Bacillus subtilis. Further analysis indicated that children with positive bacterial growth had an insignificant predictive value of CRP (2.32–7.16 mg/dl). The total white cell counts were 2.97-7.33 x 109/L despite increased lymphocyte values in the bacteria-positive blood culture. Platelet counts were also within normal limits except for a single case of H. influenzae infection (685.50 x 109/L). Interestingly, 95.01% of patients were treated with antibiotics; 66.23% of RSV infection cases were administered with a combination of antibiotics and 33.77% with only a single antibiotic. The data indicate that the use of antibiotics, either singly or in combination, is not always effective in treating LRTI in infants. Alternative therapeutic regimens should be considered, especially in Asian countries that may have limited resources.